CORPORATE STORYTELLING - L. Minaeva (Вестник университета)
The article outlines the essence and different forms of corporate storytelling as a communication management tool. Professional communicators use storytelling to achieve and manipulate various target audiences, both internal and external. The article argues that at present to be interesting for key publics stories should be told by means of various media and presuppose the active participation on the part of recipients.